Determination of Tributyltin in Seafood Based on Magnetic Molecularly Imprinted Polymers Coupled with High-Performance Liquid Chromatography-Inductively Coupled Plasma Mass Spectrometry - Hua Yang; Huien Zhang; Xiao Yan Zhu; Shi Da Chen; Lijun Liu; Daodong Pan (Journal of Food Quality)
In this study, Fe3O4 was adopted as a carrier for surface molecular imprinting with two-stage polymerization. First, the functional monomer (methacrylic acid, MAA) was modified on the surface of Fe3O4, which was then polymerized with the template molecule (tributyltin, TBT), cross linking agent (ethylene glycol dimethacrylate, EGDMA), and porogen (acetonitrile), hereby successfully preparing Fe3O4@MIPs prone to specifically identify TBT. The physical properties of Fe3O4@MIPs were then characterized, and adsorption and selection capacities were also assessed. Compared with conventional imprinting polymers, this magnetic molecular imprinting polymer (MIP) displayed significantly increased and more specific adsorption. Meanwhile, its pretreatment was simpler and faster due to magnetic separation characteristics. Using magnetic MIPs as adsorbents for enrichment and separation, detection limit, recovery rate, and linear range were 1.0 ng g−1, 79.74–95.72%, and 5 ng g−1~1000 ng g−1, respectively, for a number of seafood samples. High-performance liquid chromatography-inductively coupled plasma mass spectrometry (HPLC-ICP-MS) was used to analyze Tegillarca granosa, mussels, large yellow croaker, and other specimens, with recovery rates of 79.74–95.72% and RSD of 1.3%–4.7%. Overall, this method has a shorter total analysis time, lower detection limit, and wider linear range and can be more effectively applied to determine MAA in seawater and seafood.